Morphine induces albuminuria by compromising podocyte integrity. - Xiqian Lan; Partab Rai; Nirupama Chandel; Kang Cheng; Rivka Lederman; Moin A Saleem; Peter W Mathieson; Mohammad Husain; John T Crosson; Kalpna Gupta; Ashwani Malhotra; Pravin C Singhal (PLoS ONE)
Morphine has been reported to accelerate the progression of chronic kidney disease. However, whether morphine affects slit diaphragm (SD), the major constituent of glomerular filtration barrier, is still unclear. In the present study, we examined the effect of morphine on glomerular filtration barrier in general and podocyte integrity in particular. Mice were administered either normal saline or morphine for 72 h, then urine samples were collected and kidneys were subsequently isolated for immunohistochemical studies and Western blot. For in vitro studies, human podocytes were treated with morphine and then probed for the molecular markers of slit diaphragm. Morphine-receiving mice displayed a significant increase in albuminuria and showed effacement of podocyte foot processes. In both in vivo and in vitro studies, the expression of synaptopodin, a molecular marker for podocyte integrity, and the slit diaphragm constituting molecules (SDCM), such as nephrin, podocin, and CD2-associated protein (CD2AP), were decreased in morphine-treated podocytes. In vitro studies indicated that morphine modulated podocyte expression of SDCM through opiate mu (MOR) and kappa (KOR) receptors. Since morphine also enhanced podocyte oxidative stress, the latter seems to contribute to decreased SDCM expression. In addition, AKT, p38, and JNK pathways were involved in morphine-induced down regulation of SDCM in human podocytes. These findings demonstrate that morphine has the potential to alter the glomerular filtration barrier by compromising the integrity of podocytes.